Pengaruh Semangat Berbisnis dan Kompetensi terhadap Minat Berwirausaha pada Alumni Akademi Komunitas Dharma Bhakti Bangka - Dedi Susanto; Burhanuddin Bani (JEM Jurnal Ekonomi dan Manajemen, 2019)
This study aims to determine the effect of business enthusiasm and competence on entrepreneurial interest in the Dharma Bhakti Bangka Community Academy alumni. In this study, the population was all alumni of the Dharma Bhakti Bangka Community Academy and 49 respondents took part in the study. This study collected data that was used by using a questionnaire. Data analysis uses Multiple Linear Regression Analysis to measure the effect of more than one predictor variable (independent variable) on the dependent variable. The results showed that the enthusiasm of doing business and competence simultaneously affected the interest in entrepreneurship